Analysis Of Saving Behavior In Influencing Smoking Behavior Among Young People In Surabaya - Faradilla, Nafalia Dini; Yuniningsih, Yuniningsih; Khoirotunnisa, Fani (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to analyze the impact of saving on smoking habits, especially vape use among young people in Surabaya. Using quantitative methods, this study collected data from 100 respondents through purposive sampling, focusing on teenagers who have vaped at least once a month. Measurements were taken using a likert scale questionnaire analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS version 4 software. The analysis was conducted by testing validity and construct reliability, namely outer loading, cross loading, composite reliability, and AVE values, and testing the structural model, namely R-square and path coefficient values. The findings from this study indicate that the habit of saving money has a negative impact but is not significant in relation to smoking habits. This shows that the practice of saving money in the context of financial management does not directly strengthen a person's ability to exercise self-control in reducing vape use. Individuals who are accustomed to saving money still tend to spend part of their money on vape products due to the influence of the desire for immediate gratification and pressure from their social environment. These findings indicate that although saving is a crucial element in financial management, this habit has not been successful in controlling smoking behavior